1992
DOI: 10.1115/1.2920897
|View full text |Cite
|
Sign up to set email alerts
|

Wear Debris Formation and Agglomeration

Abstract: The hypothesis that one of the primary roles of an effective lubricant is to prevent wear particle agglomeration, thus reduce the plowing of the interfaces by the particles, and lower the frictional force, has been tested through a series of experiments and modeling. The friction coefficient, and the interfacial separation of the sliding surfaces due to entrapped wear particles, were measured on a number of sliding pairs in both dry and lubricated sliding. The results showed that the particle size, even during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 0 publications
2
25
0
1
Order By: Relevance
“…This difference should be because adhesive force between wear particles and between and contact surfaces are somehow weakened by the lubricant. This is consistent with the suggestion by Oktay and Suh [14] that an effective lubricant can prevent wear particles agglomeration by coating the individual wear particles well thus reducing the strength of the inter-particle bonding. Secondly, the position of particle agglomeration is different under the two conditions: in the lubricated condition wear particles are agglomerated at both the sides of the contact area.…”
Section: Methodssupporting
confidence: 81%
“…This difference should be because adhesive force between wear particles and between and contact surfaces are somehow weakened by the lubricant. This is consistent with the suggestion by Oktay and Suh [14] that an effective lubricant can prevent wear particles agglomeration by coating the individual wear particles well thus reducing the strength of the inter-particle bonding. Secondly, the position of particle agglomeration is different under the two conditions: in the lubricated condition wear particles are agglomerated at both the sides of the contact area.…”
Section: Methodssupporting
confidence: 81%
“…However, as the particle size rises or extensive agglomeration takes place, the friction coefficient increases again. Studies with undulated metal surfaces showed that friction values remain low when debris is entrapped within depressions [35]. In the present investigation it was shown that electrochemically microtextured surfaces have the potential to lower wear and prevent agglomeration on the articulating surfaces by fixing wear particles in the microscopic topography.…”
Section: Discussionmentioning
confidence: 94%
“…In the sliding wear of metals [31], after the generation and agglomeration of wear particles in the initial wear, the severity of sliding friction depends strictly on the adhesive interactions of the wear debris. Therefore the role of a lubricant is related to the breaking or weakening of the interfacial bonding.…”
Section: Effect Of Tribofilm Formation On the Friction And Wear Behavmentioning
confidence: 99%